2020
DOI: 10.1182/blood.2019002121
|View full text |Cite
|
Sign up to set email alerts
|

Integrated drug profiling and CRISPR screening identify essential pathways for CAR T-cell cytotoxicity

Abstract: Chimeric antigen receptor (CAR) T-cell therapy has proven effective in relapsed and refractory B-cell malignancies, but resistance and relapses still occur. Better understanding of mechanisms influencing CAR T-cell cytotoxicity and the potential for modulation using small-molecule drugs could improve current immunotherapies. Here, we systematically investigated druggable mechanisms of CAR T-cell cytotoxicity using >500 small-molecule drugs and genome-scale CRISPR-Cas9 loss-of-function screens. We identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
140
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(148 citation statements)
references
References 64 publications
7
140
1
Order By: Relevance
“…The Jurkat leukemic T-cell line is a widely used model system for the study of TCR function, 21 and we previously developed a triple parameter TCR signalling reporter cell line (TPR) based on the Jurkat line E6.1. 22 These reporter cells have been proven to be highly suitable to evaluate costimulatory pathways and the function of chimeric antigen receptors, [23][24][25] but to date, their potential to evaluate transgenically expressed TCRs in a high-throughput manner that still reflects physiological T-cell biology as seen in primary human T cells had not been tested. To facilitate highly sensitive and unbiased TCR functional characterisation, we introduced two additional modifications in the TPR cell line.…”
Section: Introductionmentioning
confidence: 99%
“…The Jurkat leukemic T-cell line is a widely used model system for the study of TCR function, 21 and we previously developed a triple parameter TCR signalling reporter cell line (TPR) based on the Jurkat line E6.1. 22 These reporter cells have been proven to be highly suitable to evaluate costimulatory pathways and the function of chimeric antigen receptors, [23][24][25] but to date, their potential to evaluate transgenically expressed TCRs in a high-throughput manner that still reflects physiological T-cell biology as seen in primary human T cells had not been tested. To facilitate highly sensitive and unbiased TCR functional characterisation, we introduced two additional modifications in the TPR cell line.…”
Section: Introductionmentioning
confidence: 99%
“…In order to elucidate the possible combinatorial role of anti-cancer or other drugs in preventing resistance to CAR T-cell immunotherapy, i.e., immunomodulatory impacts of drugs on cytotoxic properties of effector T-cells, and to explore the mechanism of CAR T-cell cytotoxicity, a detailed in vitro loss-of-function screening by means of CRISPR has conducted recently. The results revealed that cancer genetics affects the output of CAR T-cell therapy and also introduced the key role of signaling by death receptors in cytotoxic mechanism of CAR T-cells [ 150 ].…”
Section: The Deluxe Zone Of Cancer Therapy Where Crispr Meets Immunomentioning
confidence: 99%
“…For example, even in the absence of tonic signaling, how continuous presence of an auto or alloantigen would affect a CAR-or TCRengineered Tregs will be an important consideration. The metabolic phenotype of exhausted Tregs suggests that, as for CD8 + T cells and CD4 + T convs, strategies to modulate signaling pathway activity for example by use of kinase inhibitors (Dufva et al, 2020;Mestermann et al, 2019;Weber et al, 2019;Weber et al, 2020b), or modulation of transcription factor expression Lynn et al, 2019), could be strategies to limit this risk.…”
Section: Ts-car Tregs Are Dysfunctional In Vivo But Not In Vitromentioning
confidence: 99%